PEMBELAJARAN MATEMATIKA USIA SD/MI MENURUT TEORI BELAJAR PIAGET - Hidayati, Kurnia (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2012)
Abstract: Mathematics is a science related to the abstract views/concepts arranged hierarchically with the use of deductive reasoning. This is contrary to the nature of young learnersâ learning development in which they are still at the stage of concrete thinking. In accord to these, it seems quite hard for elementary students to learn mathematics that considered as abstract in nature as they have concrete way of thinking. Hence, Piaget endeavored to bridge the two conflicting phenomena by providing the four stages of learning mathematics, such as the stage of concrete, semi-concrete, semi-abstract and abstract. By using these four stages, it is expected that all educators can facilitate the students in learning mathematics optimally, in so doing, the abstract concept of mathematics can be easily understood by learners at SD / MI whose way of thinking is still concrete.